The VCU Pressure Ulcer Summit—Developing Centers of Pressure Ulcer Prevention Excellence: A Framework for Sustainability. Issue 2 (March 2016) - Creehan, Sue; Cuddigan, Janet; Gonzales, Dana; Nix, Denise; Padula, William; Pittman, Joyce; Pontieri-Lewis, Vicky; Walden, Christine; Wells, Belinda; Wheeler, Robinetta
Abstract : Hospital-acquired pressure ulcer occurrences have declined over the past decade as reimbursement policies have changed, evidence-based practice guidelines have been implemented, and quality improvement initiatives have been launched. However, the 2006–2008 Institute for Healthcare Improvement goal of zero pressure ulcers remains difficult to achieve and even more challenging to sustain. Magnet hospitals tend to have lower hospital-acquired pressure ulcer rates than non-Magnet hospitals, yet many non-Magnet hospitals also have robust pressure ulcer prevention programs. Successful programs share commonalities in structure, processes, and outcomes. A national summit of 55 pressure ulcer experts was convened at the Virginia Commonwealth University Medical Center in March 2014. The group was divided into 3 focus groups; each was assigned a task to develop a framework describing components of a proposed Magnet-designated Center of Pressure Ulcer Prevention Excellence. Systematic literature reviews, analysis of exemplars, and nominal group process techniques were used to create the framework. This article presents a framework describing the proposed Magnet-designated Centers of Pressure Ulcer Prevention Excellence. Critical attributes of Centers of Excellence are identified and organized according to the 4 domains of the ANCC model for the Magnet Recognition Program: transformational leadership; structural empowerment; exemplary professional practice; and new knowledge innovation and improvements. The structures, processes, and outcome measures necessary to become a proposed Center of Pressure Ulcer Prevention Excellence are discussed. Abstract : Supplemental Digital Content is Available in the Text.